Representações sociais dos Agentes Comunitários de Saúde sobre a violência doméstica contra as mulheres em um município de fronteira - Mello, Rafaela Zago de (2025)
Violence against women is a public health issue and has been the subject of prominent debate in recent years. The border is a place of intense foot trafficking, where vulnerability to violence is higher, requiring an urgent response from health services. In this regard, primary health care can establish a close relationship with women to get to identify the violence, with the help of community health workers, professionals who are closer to the population, integrated into the territory, and who face the demands of domestic violence against women on a daily basis. The objective of this research was to describe the social representations of community health workers in a border municipality regarding domestic violence against women. This is a qualitative, exploratory, and descriptive study conducted in two stages and based on the Social Representation Theory. The first stage involved the participation of 52 CHWs between November 2024 and March 2025 and consisted of free word association, using an online form, to evoke the five main words associated with the term “domestic violence against women”, in addition to the collection of sociodemographic data. In the second stage, online interviews took place using a semi-structured script between May and July 2025 with seven community agents who had participated in the first stage. For the analysis of the data from the first stage, prototypical analysis of free evocations was used with the OpenEvoc application and descriptive analysis of sociodemographic data with absolute and relative frequency calculations. For the second stage, a thematic analysis of the Minayo content of the interviews was carried out after full transcription. The Unioeste Research Ethics Committee, under Decision 7.049.576, approved the research. It was observed that the core of the evocations consisted mainly of terms related to physical violence, highlighting aggression, fear, pain, and abuse, while the suburbs included terms such as insecurity, dependence, impunity, injustice, and death. After thematic analysis, four categories emerged: community health workers' perceptions of domestic violence against women; community health workers' actions in response to domestic violence against women; the border and ethnic-racial diversity in the context of community health workers' actions in responding to domestic violence against women; and the network of care for women victims of domestic violence. The interviewees identified sexism, intergenerational violence, and individual behaviors as causes of domestic violence against women. The actions of the community health workers is to refer the population to the designated referral team. The research concluded that community health workers recognize domestic violence as a health problem that should be identified in primary care, but they perceivetheir role as limited, as assistants in the referral process. The findings reinforce the need for greater training and integration of the care network in order to expand the role of community health workers in the fight against violence against women, especially in the border region, due to the difficulties encountered in caring for the migrant population in situations of violence against women.